Women's Adventures in Science Seven-Volume Set (The National Academies Press)
What would it be like to build the first robot that could interact with people? Or to study human remains in search of criminal evidence? In Women's Adventures in Science, readers will learn about the trailblazing women who are leaders in a variety of scientific fields, from robotics to forensics. Each book focuses on the life and work of a woman active in her field today, providing readers with insights into the personal and professional paths that led to their careers in science. The companion Web site, www.iwaswondering.org, offers another way to "meet" these inspiring women scientists. The fun, interactive site builds on the content of the books and includes games, comic strips, videos, activities, and a timeline of women in science. Three titles from the original Women's Adventures in Science series, Strong Force, Beyond Jupiter, and Forecast Earth, are no longer available.
Keywords: Biography and Autobiography

Legal Issues and Emerging Technologies - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The nation’s 6,800 plus public transportation agencies need to have access to a program that can provide authoritatively researched, specific studies of legal issues and problems having national significance and application to the public transportation industry. Some legal issues and problems are unique to transit agencies. The TRB Transit Cooperative Research Program's TCRP Legal Research Digest 59: Legal Issues and Emerging Technologies provides transportation attorneys with guidance and resources to assist with these legal changes resulting from the implementation of technology, including regulatory challenges, risk management, cybersecurity, privacy, handling confidential and proprietary information, intellectual property rights, civil rights and environmental justice compliance, labor and employment law, and procurement issues.
Keywords: Transportation and Infrastructure

The Coast Guard’s Next Decade: An Assessment of Emerging Challenges and Statutory Needs - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
In the face of climate change, technological innovation, and global strategic competition, the U.S. Coast Guard will need to respond to many developments in the maritime domain over the next decade. The Coast Guard likely has sufficient statutory authority to respond to most of these developments, but some developments may call for new or clarified statutory authority as well as coordination with international bodies. Current statutory manning requirements, for example, will limit the Coast Guard’s ability to authorize the regulated use of uncrewed vessels with autonomous systems. New authority may also be needed to establish spaceflight-related safety zones applicable to foreign-flagged vessels within 200 nautical miles of the U.S. coastlines.These are among the findings in TRB Special Report 346: The Coast Guard’s Next Decade: An Assessment of Emerging Challenges and Statutory Needs from the Transportation Research Board of the National Academy of Sciences, Engineering, and Medicine.The report emphasizes that in addition statutory authority, the Coast Guard will need key organizational and operational capabilities, including a well-trained workforce, to respond to future challenges. A short video charts the Coast Guard's next decade.
Keywords: Transportation and Infrastructure

Emerging Challenges to Priced Managed Lanes - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
There is a wide disparity between the goals that state departments of transportation (DOTs) have for priced managed lanes and the public assumption for those goals. The public tends to be highly skeptical of priced managed lanes because the concept is difficult to explain to a nontechnical audience.The TRB National Cooperative Highway Research Program's NCHRP Synthesis 559: Emerging Challenges to Priced Managed Lanes provides an overview of the state of the practice of how state DOTs address challenges to implementing tolling, or pricing, on their managed lane systems.The synthesis entailed an extensive literature review of 60 publications and over 700 online media articles, a survey distributed to all 50 state DOTs, and a sampling of six case examples that explained specific examples of how agencies addressed challenges.
Keywords: Transportation and Infrastructure

Emerging Stronger from COVID-19: Priorities for Health System Transformation - National Academy of Medicine (The National Academies Press, 2023)
In mid-2022, the United States has lost more than 1 million people to the COVID-19 pandemic. We have been real-time witnesses to scores of heroic responses to the disease, death, inequity, and economic strife unleashed by the virus, but have also experienced the consequences of poor pandemic preparedness and long-standing structural failures in our health system. For decades, the U.S. health system has fallen far short of its potential to support and improve individual and population health. The COVID-19 pandemic has presented death and devastation—but also an unprecedented opportunity to truly transform U.S. health, health care, and health delivery. To capitalize on this opportunity, the National Academy of Medicine gathered field leaders from across all of the major health system sectors to assess how each sector has responded to the pandemic and the opportunities that exist for health system transformation. The opportunity is now to capitalize on the hard-won lessons of COVID-19 and build a health care system that centers patients, families, and communities; cares for clinicians; supports care systems, public health, and biomedical research to perform at the best of their abilities; applies innovations from digital health and quality, safety, and standards organizations; and encourages health care payers and health product manufacturers and innovators to produce products that benefit all.
Keywords: Health and Medicine

The Role of Science in Solving the Earth's Emerging Water Problems - National Academy of Sciences (The National Academies Press, 2005)
Earth is about 70% water, the human body is about 53% water, plants use water's unique properties to transport food, and aquatic organisms can survive during the winter due to water's thermal properties. However, as life continues to evolve on Earth, new problems with water emerge. The Sackler NAS Colloquium The Role of Science in Solving the Earth Emerging Water Problems provides a look into these problems ranging from water's agricultural use and importance in society to its scarcity and use in technology.
Keywords: Earth Sciences; Environment and Environmental Studies

Storms from the Sun: The Emerging Science of Space Weather - Carlowicz, Michael J.; Lopez, Ramon E. (The National Academies Press, 2002)
From the casual conversation starter to the 24-hour cable channels and Web sites devoted exclusively to the subject, everyone talks about weather. There's even weather in space and it's causing major upsets to our modern technological world. Space weather is all around us. There are no nightly news reports on space weather (yet), but we're rapidly developing the tools necessary to measure and observe trends in cosmic meteorology. New probes are going on-line that help us monitor the weather taking place miles above the Earth. But why does space weather matter? It doesn't affect whether we bring an umbrella to work or require us to monitor early school closings. It's far, far away and of little concern to us . . . right? March 13, 1989. The Department of Defense tracking system that keeps tabs on 8,000 objects orbiting Earth suddenly loses track of 1,300 of them. In New Jersey, a $10 million transformer is burned up by a surge of extra current in the power lines. Shocks to a power station in Quebec leave 6 million people without electricity. New England power stations struggle to keep their power grid up. Listeners tuning in to their local stations in Minnesota hear the broadcasts of the California Highway Patrol. Residents of Florida, Mexico, and the Grand Cayman Islands see glowing curtains of light in the sky. All of these bizarre, and seemingly unconnected, events were caused by a storm on the Sun and a fire in the sky. A series of solar flares and explosions had launched bolts of hot, electrified gas at the Earth and stirred up the second largest magnetic storm in recorded history. Before rockets and radio and the advent of other modern devices, we probably would never have noticed the effects of this space storm. But in today's electrically powered, space-faring world, the greatest space storm of the twenty-second solar maximum rang like a wake-up call. And we are now in the midst of another solar maximum, the effects of which are expected to be felt all the way through the year 2004. Storms from the Sun explores the emerging physical science of space weather and traces its increasing impact on a society that relies on space-based technologies. Authors Carlowicz and Lopez explain what space weather really means to us down here, and what it may mean for future explorations and colonization of distant worlds. By translating the findings of NASA and other top scientists into fascinating and accessible descriptions of the latest discoveries, we are privy to some of the most closely held secrets that the solar terrestrial system has to offer.
Keywords: Explore Science; Space and Aeronautics

Emerging Hazards in Commercial Aviation—Report 1: Initial Assessment of Safety Data and Analysis Processes - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Commercial aviation safety in the United States has improved more than 40-fold over the last several decades, according to industry statistics. The biggest risks include managing safety in the face of climate change, increasingly complex systems, changing workforce needs, and new players, business models, and technologies. TRB Special Report 344: Emerging Hazards in Commercial Aviation—Report 1: Initial Assessment of Safety Data and Analysis Processes is the first of a series of six reports that will be issued from TRB and the National Academies of Sciences, Engineering, and Medicine over the next 10 years on commercial aviation safety trends in the U.S.
Keywords: Transportation and Infrastructure

Guidebook for Managing Data from Emerging Technologies for Transportation - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
With increased connectivity between vehicles, sensors, systems, shared-use transportation, and mobile devices, unexpected and unparalleled amounts of data are being added to the transportation domain at a rapid rate, and these data are too large, too varied in nature, and will change too quickly to be handled by the traditional database management systems of most transportation agencies.The TRB National Cooperative Highway Research Program's NCHRP Research Report 952: Guidebook for Managing Data from Emerging Technologies for Transportation provides guidance, tools, and a big data management framework, and it lays out a roadmap for transportation agencies on how they can begin to shift – technically, institutionally, and culturally – toward effectively managing data from emerging technologies.Modern, flexible, and scalable “big data” methods to manage these data need to be adopted by transportation agencies if the data are to be used to facilitate better decision-making. As many agencies are already forced to do more with less while meeting higher public expectations, continuing with traditional data management systems and practices will prove costly for agencies unable to shift.Supplemental materials include an Executive Summary, a PowerPoint presentation on the Guidebook, and NCHRP Web-Only Document 282: Framework for Managing Data from Emerging Transportation Technologies to Support Decision-Making.
Keywords: Transportation and Infrastructure

Existing and Emerging Highway Infrastructure Preservation, Maintenance, and Renewal Definitions, Practices, and Scenarios - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
The National Cooperative Highway Research Program's NCHRP Web-Only Document 272: Existing and Emerging Highway Infrastructure Preservation, Maintenance, and Renewal Definitions, Practices, and Scenarios provides appendices to NCHRP Report 750, Volume 7: Preservation, Maintenance, and Renewal of Highway Infrastructure.
Keywords: Transportation and Infrastructure

Dynamic Curbside Management: Keeping Pace with New and Emerging Mobility and Technology in the Public Right-of-Way, Part 1: Dynamic Curbside Management Guide and Part 2: Conduct of Research Report - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Dynamic curbside management has been the purview of cities, with much of the relevant research and guidance directed toward local transportation agencies. However, state departments of transportation, metropolitan planning organizations, and other regional agencies can be important partners for these local entities because, in many cases, roadways and other curb zone elements are part of the regional or state network.The TRB National Cooperative Highway Research Program's NCHRP Web-Only Document 340: Dynamic Curbside Management: Keeping Pace with New and Emerging Mobility and Technology in the Public Right-of-Way, Part 1: Dynamic Curbside Management Guide and Part 2: Conduct of Research Report is designed to help practitioners at state DOTs, MPOs, and local jurisdictions build data-driven understanding, allocation, and operation of the curb based on community values.Supplemental to the document are a Quick Start Summary of the research and a Presentation summarizing the project.
Keywords: Transportation and Infrastructure

Taking Stock of Science Standards Implementation: Proceedings of a Virtual Summit - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
On October 14 and 15, and December 8, 2021, the Board on Science Education at the National Academies of Sciences, Engineering, and Medicine held a virtual Summit entitled Taking Stock of Science Standards Implementation. Participants explored the landscape of state science standards implementation, identified where there have been successes and challenges, and determined next steps and the resources needed for continuing or re-invigorating implementation efforts. This publication summarizes the presentations and discussion of the event.
Keywords: Education

Origins, Worlds, and Life: Planetary Science and Astrobiology in the Next Decade - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The next decade of planetary science and astrobiology holds tremendous promise. This booklet highlights key science questions, identifies priority missions, and presents a research strategy that includes both planetary defense and human exploration.
Keywords: Space and Aeronautics

Rise and Thrive with Science: Teaching PK-5 Science and Engineering - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Research shows that that children learn science and engineering subjects best by engaging from an early age in the kinds of practices used by real scientists and engineers. By doing science and engineering, children not only develop and refine their understanding of the core ideas and crosscutting concepts of these disciplines, but can also be empowered to use their growing understanding to make sense of questions and problems relevant to them. This approach can make learning more meaningful, equitable, and lasting. Using cases and shorter examples, Rise and Thrive with Science shows what high-quality teaching and learning in science and engineering can look like for preschool and elementary school children. Through analyses of these examples and summaries of research findings, the guide points out the key elements of a coherent, research-grounded approach to teaching and learning in science and engineering. This guide also discusses the kinds of support that educators need to implement effective and equitable instruction for all children. This book will provide inspiration for practitioners at the preschool and elementary levels to try new strategies for science and engineering education, whatever their level of experience. Rise and Thrive with Science will be an essential guide for teachers as they organize instruction to enable young children to carry out their own science investigations and engineering design projects, determine the kinds of instruction that lead to meaningful learning, and try to engage every one of their students.
Keywords: Education

Roots and Trajectories of Violent Extremism and Terrorism: A Cooperative Program of the U.S. National Academy of Sciences and the Russian Academy of Sciences (1995-2020) - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
During the past 25 years, the U.S. National Academies of Sciences, Engineering, and Medicine, in collaboration with the Russian Academy of Sciences, have carried out a wide variety of activities to improve understanding of the challenges in containing and reducing ethnic conflicts, violent extremism, and terrorism. Roots and Trajectories of Violent Extremism and Terrorism provides an overview of this cross-ocean program, which has involved American and Russian scientists, engineers, and medical professionals from a large number of government agencies, leading research institutions, think tanks, educational institutions, analytical centers, and consulting and commercial firms in the two countries. This report highlights challenges addressed by the academies over many years that remain of current interest as the U.S., Russian, and other governments continue to cope with old and new forms of aggression that threaten the livelihood of populations at home and abroad.
Keywords: Conflict and Security Issues

Emerging Technologies for Construction Delivery - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The uses and levels of maturity of five advanced technology areas visualization and modeling, interconnected technologies, safety technologies, instrumentation and sensors, and unmanned aircraft systems in transportation highway construction projects are documented in TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 534: Emerging Technologies for Construction Delivery. The synthesis also investigates the implementation barriers and success factors for these technology areas and discusses the lessons learned as noted by state DOTs in their effort to study, test, and implement a new construction technology.As the highway construction industry infuses more technologies into the process of project delivery, state DOTs have an opportunity to realize improved project performance regarding cost, schedule, and quality.The Federal Highway Administration (FHWA) Every Day Counts (EDC) initiatives promote the use of various advanced and emerging technologies (e.g., automated machine guidance, unmanned aircraft systems, building information modeling, handheld instruments and devices, and work zone intrusion detection systems).
Keywords: Transportation and Infrastructure

Ontologies in the Behavioral Sciences: Accelerating Research and the Spread of Knowledge: Digest Version - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Ontologies in the Behavioral Sciences: Accelerating Research and the Spread of Knowledge describes how ontologies support science and its application to real-world problems. That report details how ontologies function, how they can be engineered to better support the behavioral sciences, and the resources needed to sustain their development and use to help ensure the maximum benefit from investment in behavioral science research. The full report published in May, 2022. This digest version summarizes the primary ideas presented in that report.
Keywords: Behavioral and Social Sciences

Roundtable on Data Science Postsecondary Education: A Compilation of Meeting Highlights - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Established in December 2016, the National Academies of Sciences, Engineering, and Medicine's Roundtable on Data Science Postsecondary Education was charged with identifying the challenges of and highlighting best practices in postsecondary data science education. Convening quarterly for 3 years, representatives from academia, industry, and government gathered with other experts from across the nation to discuss various topics under this charge. The meetings centered on four central themes: foundations of data science; data science across the postsecondary curriculum; data science across society; and ethics and data science. This publication highlights the presentations and discussions of each meeting.
Keywords: Education; Computers and Information Technology; Math, Chemistry, and Physics

Teaching K-12 Science and Engineering During a Crisis - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
The COVID-19 pandemic is resulting in widespread and ongoing changes to how the K-12 education system functions, including disruptions to science teaching and learning environments. Students and teachers are all figuring out how to do schooling differently, and districts and states are working overtime to reimagine systems and processes. This is difficult and stressful work in the middle of the already stressful and sometimes traumatic backdrop of the global pandemic. In addition, students with disabilities, students of color, immigrants, English learners, and students from under-resourced communities have been disproportionately affected, both by the pandemic itself and by the resulting instructional shifts. Teaching K-12 Science and Engineering During a Crisis aims to describe what high quality science and engineering education can look like in a time of great uncertainty and to support practitioners as they work toward their goals. This book includes guidance for science and engineering practitioners - with an emphasis on the needs of district science supervisors, curriculum leads, and instructional coaches. Teaching K-12 Science and Engineering During a Crisis will help K-12 science and engineering teachers adapt learning experiences as needed to support students and their families dealing with ongoing changes to instructional and home environments and at the same time provide high quality in those experiences.
Keywords: Education

Population Health Science in the United States: Trends, Evidence, and Implications for Policy: Proceedings of a Joint Symposium - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
On October 3, 2018, the Roundtable on Population Health Improvement of the National Academies of Sciences, Engineering, and Medicine and the Interdisciplinary Association for Population Health Science convened a joint symposium in Washington, DC to consider the current state of population health science in the United States. At the symposium, speakers and participants reviewed the status of population health in the United States, including current trends in health and mortality, and racial, ethnic, and socioeconomic disparities; explored the complexities of policy implementation with attention to evidence generation and to surfacing and mitigating negative unintended consequences of policies for population health; and shared perspectives on finding common ground to move population health forward. This publication summarizes the presentation and discussion of the workshop.
Keywords: Health and Medicine